منهجية تجديد الخطاب الصوفي وآلياته - خميس, نادية (قــــــراءات, 2019)
تسعى هذه المقاربة التي نريد استجلاء أوصافها، التعرض بالتحليل لراهن الخطاب الصوفي الذي تتجاذبه دعاوى التنظير والتسليك من جهة ودعوى التغييب والإقصاء من جهة أخرى. إن إشكالية عدم الفهم لهذا الخطاب نجدها تنبعث من تلك القراءات المغيّبة لوعيه الشمولي؛ وعي لا يفقهه إلامن استوعب ملامح الائتلاف في بنيته العميقة الملتحفة بالبنى السطحية ومظاهر اختلافها. فكان لهذا الوعي / الرؤية أن مكّن الخطاب من التملص عما هو سائد من نظم فكرية بمنهج تأويلي يتسلح بآليات منتجة تقوم على أساسيات الفهم / الفعل / الحضور؛ حضور فعل المشاهدة كرؤية جوهرية إحيائية يتحقق بها إنسان الحاضر والحضور.. وهنا تكون معالم التجديد في هذا الخطاب. Abstract This approach that we want to clarify its description seeks to analyze the mystic discourse, which is beset by the calls of theorizing on the one hand and the calls of absence and exclusion on the other hand. The problem of lack of understanding of this discourse comes out from the excluding readings of its comprehensive consciousness which is grasped only by those who understand its features of the coalition in the deep structure which is covered with surface structures with its features of disagreement. This consciousness/vision enabled the discourse to get rid of the prevailing intellectual trends which support the interpretive approach. This approach is equipped with productive mechanisms based on the principles of comprehension, action, and the presence of the witnessing act that is substantial and resuscitative vision by which a human of the present and the presence is realized…and here exists the landmarks of renewal in this discourse.